Stabilized nanosilver based antimicrobial poly(3-hydroxybutyrate-co-3-hydroxyvalerate) nanocomposites of interest in active food packaging. (February 2016) - Castro-Mayorga, J.L.; Fabra, M.J.; Lagaron, J.M.
Abstract: Antimicrobial silver based nanocomposites of poly(3-hydroxybutyrate-co-3-hydroxyvalerate) were successfully synthesized and characterized. For the synthesis, a masterbatch of in situ stabilized silver nanoparticles (AgNPs) produced into a mixed microbial cultures based poly(3-hydroxybutyrate-co-18 mol%-3-hydroxyvalerate) (PHBV18) was used, which was diluted by melt compounding with a commercial poly(3-hydroxybutyrate-co-3 mol%-3-hydroxyvalerate) (PHBV3) material. The incorporated AgNPs (0.04 wt.%) led to a surprising oxygen permeability drop of ca . 56% compared to the neat polymer. The thermal stability and optical properties of the nanocomposites were not significantly modified as compared to the neat PHBV3. Moreover, the antimicrobial performance of the PHBVs-AgNPs films against two of the most common food borne pathogens, Salmonella enterica and Listeria monocytogenes, showed a strong and sustained (even after seven-months) antibacterial activity. This study provides an innovative route to generate fully renewable and biodegradable antimicrobial nanocomposites that could potentially be of interest in film and coating applications such as active food packaging. Industrial relevance: As a response to the consumers for more safety foodstuffs and ecofriendly packaging materials, this work presents a novel methodology to develop antimicrobial packaging by using biodegradable materials obtained from industrial food by-products in combination of an industrially meaningful melt blending process. The methodology here applied allows the use of low doses of stabilized silver nanoparticles in the polymer matrix, without additives, which exhibits prolonged antimicrobial activity against food borne pathogens and enhanced oxygen barrier properties. These materials are of great interest in the development and design of biodegradable active food packaging materials and antibacterial food contact surfaces with the additional advantage that they can be easily scale-up. Graphical abstract: Highlights: AgNPs were stabilized by mixed microbial culture PHBV obtained from by-products Colourless PHBV/AgNPs nanocomposites were prepared by melt blending process AgNPs enhanced oxygen barrier up to 56% as compared to the neat polymer The antimicrobial activity of PHBV/AgNPs was evaluated against food borne pathogens Nanocomposites had prolonged biocide effect at very low AgNPs content (0.04 wt.-%)